(untitled) (Management Studies and Business Journal (PRODUCTIVITY), 2025)
In the ever-evolving digital era, digital transformation has become a major force driving the integration of Environmental, Social, and Governance (ESG) principles in various industrial sectors. This article aims to narratively examine how digital transformation contributes to ESG implementation, by reviewing academic literature and industry reports from the last five to ten years. The study was conducted using a narrative literature review approach with a focus on three ESG dimensions, namely environmental, social, and governance. The results of the study show that digitalization drives energy efficiency, green innovation, and emission reduction in the environmental sector; strengthens social inclusion, human resource development, and access to services in the social aspect; and improves transparency, accountability, and oversight systems in organizational governance. However, there are challenges such as the digital divide, data ethics risks, and technological bias, especially in developing countries. This article also highlights significant differences in infrastructure readiness and capabilities between developed and developing countries. By presenting cross-sector thematic mapping, this article is expected to be a conceptual and practical reference for academics, industry players, and policy makers in designing digital transformation strategies that are aligned with global sustainability goals.